Daftar Isi Jurnal Biosel - Editor Editor (BIOSEL (Biology Science and Education): Jurnal Penelitian Science dan Pendidikan, 2019)
Journal biosel receiving articles of the results of the study in biology field and education. This journal rising twice a year, namely edition of january-june and edition of july-december. Editor receive writing, doing test plagyarism writing, and do review in online. Articles sent has not been seen publicly elsewhere and a maximum of the total number of pages is 15 pages